ANALISIS PENGARUH JUMLAH WISATAWAN DAN TINGKAT HUNIAN HOTEL TERHADAP PENERIMAAN DAERAH SEKTOR PARIWISATA DI KABUPATEN WAKATOBI PERIODE 2008-2017 - Prianto, Fachril (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This research aims to find out how big the influence of number of tourists visit and hotel occupancy rates against acceptance of the regional tourism sector at Wakatobi period 2008-2017. The data used in this research is quantitative approach with secondary data. The data in the form of Time Series data on the number of tourist visits, the occupancy rate for hotels and reception areas of the tourism sector in the Wakatobi. The data was processed using SPSS 16.0 application with double liner regression analysis methods. Based on the results of the study it can be concluded that partially or equally the number of tourist visits, the hotel occupancy rate effect is not significantly to acceptance of the regional tourism sector at Wakatobi. simultaneous or individual tourists visit sum effect is not significantly to acceptance of the regional tourism sector, this means many tourists visit sum not yet influential significantly to acceptance of the area the tourism sector and the hotel occupancy rate effect is not significantly to acceptance of the regional tourism sector in Wakatobi, this means many of the least amount of hotel occupancy rates have not been significantly influential against the reception area of the tourism sector in the Wakatobi during the period 2008-2017.